1991
DOI: 10.1159/000293135
|View full text |Cite
|
Sign up to set email alerts
|

Imipramine Receptor Binding and Serotonin Uptake in Platelets of Women with Premenstrual Changes

Abstract: Gonadal hormones are believed to be involved in the pathophysiology of premenstrual changes (PMC) possibly through their interaction with neurotransmitter systems in the brain. The serotonergic system, an important central modulator of mood and behavior which is involved in the pathophysiology of affective disorders has been suggested to play a role in the genesis of dysphoric PMC. Blood platelet serotonin (5-HT) uptake and imipramine (IMI) binding have been shown to share similarities with serotonergic mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 38 publications
1
20
0
2
Order By: Relevance
“…Whole blood derived during the early luteal phase of the menstrual cycle from women with PMDD was found to have decreased platelet imipramine receptor binding (a marker of serotonin activity) compared to controls. This finding was noted prior to the development of menstrual symptoms and was similar to results observed during the symptomatic phase of the cycle [44]. Interestingly, decreased supplementation of tryptophan, the precursor of serotonin, was shown to exacerbate premenstrual symptoms [45,46].…”
Section: Discussionsupporting
confidence: 81%
“…Whole blood derived during the early luteal phase of the menstrual cycle from women with PMDD was found to have decreased platelet imipramine receptor binding (a marker of serotonin activity) compared to controls. This finding was noted prior to the development of menstrual symptoms and was similar to results observed during the symptomatic phase of the cycle [44]. Interestingly, decreased supplementation of tryptophan, the precursor of serotonin, was shown to exacerbate premenstrual symptoms [45,46].…”
Section: Discussionsupporting
confidence: 81%
“…Human platelet investigations have shown increased [ 3 H] imipramine binding during the luteal phase compared with the follicular phase (Rojansky et al 1991;Steege et al 1992), although one study found no effect of the menstrual cycle phase (Poirier et al 1986). However, since platelet SERT binding appears to correlate poorly with central SERT binding (Malison et al 1998b), a direct examination of the brain is necessary.…”
Section: Effect Of Menstrual Cycle On Dat and Sert Availabilitymentioning
confidence: 99%
“…The selectivity of serotonergic abnormalities is demonstrated by the report that plasma total and free tryptophan levels were similar in women with and without PMS [25]. This notion is supported by the author's finding [30] that imipramine receptor binding (IMI) in platelets of women with dysphoric PMS was low during the late luteal phase, but not during serotonin uptake in the same platelets. This study demonstrated another principle-that IMI receptor binding, but not serotonin uptake, was lower in women with PMS compared with women without PMS also during the nonsymptomatic early luteal phase.…”
Section: Serotonergic Abnormalities In Women With Premenstrual Syndromentioning
confidence: 76%